How Do Higher Education Students In Israel Perceive The Impact Of Artificial Intelligence (AI) On The Effectiveness Of The Educational Process? - Lozyana Kabia (Journal of Informatics Education and Research, 2025)
The research investigates how students in higher education in Israel perceive the impact of Artificial Intelligence (AI) on educational process effectiveness. This study had two main motivators; the growing use of AI technology in higher education settings, and the limited research of student perspectives in the Israeli context. The study focused a qualitative method and used a sample of 50 students who participated in semi-structured interviews and focus groups were recruited to the study through snowball sampling from higher education institutions. The study discovered six significant themes, including the positive effects of AI on efficiency in learning, personalization of learning, and academic performance. The study also addressed the ethical implications of AI which contained student perspectives on privacy, equity, and implications for critical thinking. The study provides recommendations for institutional policies and practice including guidelines for equitable AI use, development of formal AI literacy programs, and training education and students. Theoretically, the research study has developed as one of the few studies that help expand knowledge of the educational implications of AI, and practically supports development of policies that protect academic integrity while maximizing benefits of holistic learner-centered experiences.